Chromosome-Specific Painting in Cucumis Species Using Bulked Oligonucleotides. Issue 3 (13th May 2015) - Han, Yonghua; Zhang, Tao; Thammapichai, Paradee; Weng, Yiqun; Jiang, Jiming
Abstract: Chromosome-specific painting is a powerful technique in molecular cytogenetic and genome research. We developed an oligonucleotide (oligo)-based chromosome painting technique in cucumber ( Cucumis sativus ) that will be applicable in any plant species with a sequenced genome. Oligos specific to a single chromosome of cucumber were identified using a newly developed bioinformatic pipeline and then massively synthesized de novo in parallel. The synthesized oligos were amplified and labeled with biotin or digoxigenin for use in fluorescence in situ hybridization (FISH). We developed three different probes with each containing 23, 000–27, 000 oligos. These probes spanned 8.3–17 Mb of DNA on targeted cucumber chromosomes and had the densities of 1.5–3.2 oligos per kilobases. These probes produced FISH signals on a single cucumber chromosome and were used to paint homeologous chromosomes in other Cucumis species diverged from cucumber for up to 12 million years. The bulked oligo probes allowed us to track a single chromosome in early stages during meiosis. We were able to precisely map the pairing between cucumber chromosome 7 and chromosome 1 of Cucumis hystrix in a F1 hybrid. These two homeologous chromosomes paired in 71% of prophase I cells but only 25% of metaphase I cells, which may provide an explanation of the higher recombination rates compared to the chiasma frequencies between homeologous chromosomes reported in plant hybrids.